Pathobiology of myocardial and cardiomyocyte injury in ischemic heart disease: Perspective from seventy years of cell injury research - Buja, L. Maximilian (Experimental and molecular pathology, 2024)
This review presents a perspective on the pathobiology of acute myocardial infarction, a major manifestation of ischemic heart disease, and related mechanisms of ischemic and toxic cardiomyocyte injury, based on advances and insights that have accrued over the last seventy years, including my sixty years of involvement in the field as a physician-scientist-pathologist. This analysis is based on integration of my research within the broader context of research in the field. A particular focus has been on direct measurements in cardiomyocytes of electrolyte content by electron probe X-ray microanalysis (EPXMA) and Ca2+ fluxes by fura-2 microspectrofluorometry. These studies established that increased intracellular Ca2+ develops at a transitional stage in the progression of cardiomyocyte injury in association with ATP depletion, other electrolyte alterations, altered cell volume regulation, and altered membrane phospholipid composition. Subsequent increase in total calcium with mitochondrial calcium accumulation can occur. These alterations are characteristic of oncosis, which is an initial pre-lethal state of cell injury with cell swelling due to cell membrane dysfunction in ATP depleted cells; oncosis rapidly progresses to necrosis/necroptosis with physical disruption of the cell membrane, unless the adverse stimulus is rapidly reversed. The observed sequential changes fit a three-stage model of membrane injury leading to irreversible cell injury. The data establish oncosis as the primary mode of cardiomyocyte injury in evolving myocardial infarcts. Oncosis also has been documented to be the typical form of non-ischemic cell injury due to toxins. Cardiomyocytes with less energy impairment have the capability of undergoing apoptosis and autophagic death as well as oncosis, as is seen in pathological remodeling in chronic heart failure. Work is ongoing to apply the insights from experimental studies to better understand and ameliorate myocardial ischemia and reperfusion injury in patients. The perspective and insights in this review are derived from basic principles of pathology, an integrative discipline focused on mechanisms of disease affecting the cell, the organizing unit of living organisms. •Cardiomyocyte injury involves progressive membrane damage and calcium accumulation.•Oncosis (cell injury with swelling) is the primary mode of ischemic cardiomyocyte death.•Reperfusion and conditioning modulate outcomes of an ischemic insult.•Excess cardiomyocyte death contributes to myocardial remodeling and heart failure.•Insights from cell injury research can improve outcomes in heart diseases.